Herd inspections Sachsen - Anhalt (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2020)
87 JPEG files documenting participant observation during the annual herd inspection of the German Karakul Breeders' Society
Keywords: Karakul sheep; Breeding; Postcolonialism; South Africa; Agriculture; Colonisation; Germany; Namibia; Swakara; Karakul Circulations; Colonial Economies; Karakul Farming; Colonial South-West Africa; German Colonialism; Karakul Sheep Industry